Evaluation of the Pharmacokinetic Drug Interaction of Capmatinib With Itraconazole and Rifampicin and Potential Impact on Renal Transporters in Healthy Subjects - Cui, Xiaoming; Chen, Xinhui; Pognan, Nathalie; Sengupta, Tirtha; Rahmanzadeh, Gholamreza; Kornberger, Ruediger; Giovannini, Monica (Journal of clinical pharmacology, 2023)
Capmatinib is a highly specific, potent, and selective mesenchymal–epithelial transition factor inhibitor predominantly eliminated by cytochrome P450 (CYP) 3A4 and aldehyde oxidase. Here, we investigated the effects of a strong CYP3A inhibitor (itraconazole) and a strong CYP3A inducer (rifampicin) on single‐dose pharmacokinetics of capmatinib. In addition, serum creatinine and cystatin C were monitored to assess the potential inhibition of renal transporters by capmatinib. This was an open‐label, 2‐cohort (inhibition and induction), 2‐period (capmatinib alone and inhibition/induction periods) study in healthy subjects. In the inhibition cohort, capmatinib (400 mg/day) was given alone, then with itraconazole (200 mg/day for 10 days, 5‐day lead‐in before coadministration). In the induction cohort, capmatinib (400 mg/day) was given alone, then with rifampicin (600 mg/day for 9 days, 5‐day lead‐in before coadministration). Fifty‐three subjects (inhibition cohort, n = 27; induction cohort, n = 26) were enrolled. Coadministration of itraconazole resulted in an increase of capmatinib area under the plasma concentration–time curve from time 0 to infinity by 42% (geometric mean ratio [GMR], 1.42; 90%CI, 1.33–1.52) with no change in maximum plasma concentration (GMR, 1.03; 90%CI, 0.866–1.22). Coadministration of rifampicin resulted in a reduction of capmatinib area under the plasma concentration–time curve from time 0 to infinity by 66.5% (GMR, 0.335; 90%CI, 0.300–0.374) and a decrease in maximum plasma concentration by 55.9% (GMR, 0.441; 90%CI, 0.387–0.502). After a single dose of capmatinib, a transient increase in serum creatinine was observed with no change in serum cystatin C concentration during the 3‐day monitoring period. In conclusion, coadministration of itraconazole or rifampicin resulted in clinically relevant changes in systemic exposure to capmatinib. The transient increase in serum creatinine without any increase in cystatin C suggests inhibition of renal transport by capmatinib.